2018
DOI: 10.7874/jao.2017.00108
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Adaptation and Cross Language Validation of Tinnitus Handicap Inventory in Urdu

Abstract: Background and ObjectivesTinnitus is characterized as a perception of numerous auditory sounds in absence of external stimulus. Tinnitus can have a considerable consequence on a person’s quality of life, and is considered to be very complicated to quantify. The aim of this study was to investigate the reliability and validity of Urdu translation of the Tinnitus Handicap Inventory (THI) in Pakistan. It was designed to assess the presence of various auditory sounds without the external stimulus. Scale consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…To date, more than a dozen factor structure validation studies of THI have been published, with study groups ranging from 50 [ 32 , 34 ] to 373 patients [ 35 ]. The majority of these studies failed to demonstrate a three-factor structure [ 36 38 ], although two of them did support the original three-factor solution [ 35 , 39 ]. In particular, the German study seems very strong: in its confirmatory factor analysis it used a large sample of 373 tinnitus patients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than a dozen factor structure validation studies of THI have been published, with study groups ranging from 50 [ 32 , 34 ] to 373 patients [ 35 ]. The majority of these studies failed to demonstrate a three-factor structure [ 36 38 ], although two of them did support the original three-factor solution [ 35 , 39 ]. In particular, the German study seems very strong: in its confirmatory factor analysis it used a large sample of 373 tinnitus patients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…2018; Eggermont, 2012;Yıldız et al, 2017;Zoger et al, 2006). Previous research has debated the relationship between tinnitus and PP (Alpini & Cesarani, 2006;Aqeel & Ahmed, 2018;Aqeel et al, 2017;Axelsson & Ringdahl, 1989;Coelho et al, 2004;Danesh et al, 2018;Scholes & Ramakrishnan, 2015;Vanneste et al, 2018). While some studies have shown that patients with HL and tinnitus were more inclined to mood swings, stress, anxiety, and depression than those who had tinnitus without HL (Bauer et al, 2017;Cima et al, 2018;Ibarra et al, 2018;Van Damme et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Tinnitus Handicap Inventory (THI) was used to measure the levels of tinnitus perception in all participants. The THI is a 25-item scale, with three subscales, developed by Newman, Sandridge, and Jacobson (1998) and translated into Urdu by Aqeel and Ahmed (2018). This scale requires individuals to mark/rate their agreement with each item of the questionnaire, for example, 1 ( No ) to 3 ( Yes ).…”
Section: Methodology Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinnitus is more than four times common in people with hearing loss than in people without hearing loss [7]. There is a clearly high correlation between hearing impairment and tinnitus [8,9]. The prevalence of any type of tinnitus is 17-20 %, and that of persistent tinnitus is 8-10 %, in normal hearing populations [10].…”
Section: Discussionmentioning
confidence: 99%